Country risks and foreign direct investments in 7 ASEAN countries - Nguyen, Thi Lam Anh; Bach, Duc Khoi Nguyen; LE, Minh Tuan (Asian Economic and Financial Review, 2025)
This study investigates the influence of country risk on foreign direct investment (FDI) inflows in ASEAN nations over the period 1998–2022, focusing on political, economic, and financial risk components. Employing the Fixed Effects Model (FEM), this study analyzes panel data across ASEAN countries to assess how different aspects of country risk affect FDI attraction. The findings reveal that while no significant overall connection exists between country risk and FDI inflows across the entire sample, country-specific characteristics play a crucial role. Specifically, negative impacts are observed in developing nations, nations with lower FDI inflows, and those with relatively low-risk profiles. Political risks significantly discourage foreign investments, especially in developing economies, economies with difficulty attracting foreign capital, and those considered high-risk. By contrast, financial and economic risks generally exhibit no significant influence on FDI. Nonetheless, reducing economic risk emerges as an important factor for enhancing FDI in countries with low levels of FDI attraction, whereas mitigating financial risk is critical for countries that attract higher volumes of FDI. Country risk impacts FDI inflows in a nuanced, country-specific manner, with political risk being the most significant deterrent for developing and high-risk ASEAN nations. Based on this finding, we are able to provide recommendations to address distinct dimensions of country risk and foster a more favorable investment environment across ASEAN member states.